La princesse de Navarre interludes set to music by Monsieur Rameau for the comedy by Monsieur de Voltaire ; performed on the occasion on the marriage of Monseigneur le Dauphin - Rameau, Jean-Philippe 1683-1764 (Erato, 1980)
La Princesse de Navarre: Comédie-ballet en trois actes. Livret: Voltaire.
Mit Libretto in engl., franz. und dt. Sprache. - Interpr.: Hill-Smith, Marilyn [Sopr]. Harrhy, Eiddwen [Sopr]. Chambers, Frances [Sopr]. Rees, Judith [Sopr]. Goldthorpe, Michael [Ten]. Savidge, Peter [Bar]. Caddy, Ian [Bass]. Wigmore, Richard [Bass]. English Bach Festival <London; Oxford> / Baroque Orchestra. English Bach Festival <London; Oxford> / Singers. MacGegan, Nicholas [Dir.].